مساهمة تكنولوجيا المعلومات والاتصال في تحقيق الجودة بمؤسسات التعليم العالي دراسة مسحية على عينة من أساتذة قسم علوم الإعلام كلية علوم الإعلام والاتصال بجامعة الجزائر 3 - عبديش, صونية; علواش, كهينة (جامعة الوادي - University of Eloued, 2021)
يعتبر موضوع تطبيق الجودة في التعليم العالي من بين المواضيع الحديثة والمهمة التي نالت اهتمام الحكومات والمسؤولين في جميع دول العالم، للنهوض بالقطاع بما يزيد من جودة خدماتها. وقد ركز الكثير من القائمين على تطوير القطاع، لضمان الجودة وتطبيق نظامها وتطويرها بصفة مستمرة للتميز ومواكبة التطورات والتحديات العالمية، وذلك باستخدام تكنولوجيا المعلومات والاتصال للمساهمة في تحقيق الجودة بمؤسسات التعليم العالي والبحث العلمي، وبالتحديد بقسم علوم الإعلام بكلية علوم الإعلام والاتصال جامعة الجزائر 3، ومعرفة مدى تحقيق الجودة بتوظيف هذه التكنولوجيا للنهوض بالقطاع والرقي به. من هنا أتت هذه الورقة البحثية للتفصيل في ماهية الجودة في التعليم العالي، وفوائد تطبيقها، وأهدافها ثم البحث عن واقع تطبيق تكنولوجيا المعلومات والاتصال لضمان تحقيق الجودة في هذه المؤسسة الجامعية لنصل إلى التحديات التي تعيق تطبيق الجودة في قطاع التعليم العالي. Abstract: The issue of applying quality in higher education is among the modern and important topics that have attracted the attention of governments and officials in all countries of the world, to advance the sector in a manner that increases the quality of its services. Many of those in charge of developing the sector have focused on ensuring quality and applying its system and developing it on a continuous basis for keeping pace with global developments and challenges, using information and communication technology to contribute to achieving quality in institutions of higher education and scientific research, specifically in the Department of Information Sciences at the Faculty of Information and Communication Sciences, University of Algiers 3, and to identify the extent to which quality has been achieved by employing this technology to advance and develop the sector. From here came this research paper to explore the nature of quality in higher education, the benefits of its application, and its objectives, and then search for the reality of the application of information and communication technology to ensure the achievement of quality in this university institution in order to reach the challenges that hinder its application in the higher education sector.
The Contribution of Information and Communication Technology to Achieve Higher Education Institutions Quality A survey study on a sample of professors from the Department of Information Sciences, Faculty of Information and Communication Sciences, University of Algiers 3
مقال
Keywords: تكنولوجيا المعلومات والاتصال، الجودة، التعليم العالي، التكنولوجيا والجودة، جودة التعليم العالي.: Information and communication technology, quality, higher education, technology and quality, quality of higher education